Explaining money demand in China during the transition from a centrally planned to a market-based monetary system - Anne-Laure Delatte; Julien Fouguau; Carsten A. Holz (Bank of Finland, Institute for Economies in Transition (BOFIT), 2011)
We examine the transition process from a centrally planned to a market-based monetary system in China, with the objective of giving a functional form to the transition in money demand. Applying the cointegrating Time-Varying Smooth Transition Regression model proposed by Choi and Saikkonen (2004) on a constructed dataset spanning the period from 1984 to 2010, and using a seasonal unit-root test developed by Hylleberg et al. (1990), our findings invalidate much of the earlier literature. Our examination of disaggregate as well as aggregate money balances yields the following findings. (1) Households have an infinite demand for money at prevailing interest rates. (2) Enterprises have gradually gained decision-making authority over their deposits. (3) Money is a complement rather than a substitute to capital and this has become more prominent over the period. (4) The credit plan has ceased to be a significant driver of money holdings after 1997. (5) In the aggregate monetary sphere, the deposit interest rate has gained only a minor role as a monetary instrument, and only since 2000.
URN:NBN:fi:bof-201408072038
Keywords: 330